Stage‐specific differential expression of zinc transporter SLC30A and SLC39A family proteins during prostate tumorigenesis. Issue 5 (20th January 2022) - Prasad, Ram R.; Raina, Komal; Mishra, Neha; Tomar, Munendra S.; Kumar, Robin; Palmer, Amy E.; Maroni, Paul; Agarwal, Rajesh
Abstract: Prostate cancer (PCa) initiation and progression uniquely modify the prostate milieu to aid unrestrained cell proliferation. One salient modification is the loss of the ability of prostate epithelial cells to accumulate high concentrations of zinc; however, molecular alterations associated with loss of zinc accumulating capability in malignant prostate cells remain poorly understood. Herein, we assessed the stage‐specific expression of zinc transporters (ZNTs) belonging to the ZNT (SLC30A) and Zrt‐ and Irt‐like protein (ZIP) (SLC39A) solute‐carrier family in the prostate tissues of different genetically engineered mouse models (GEMM) of PCa (TMPRSS2‐ERG.Pten flox/flox, Hi‐Myc +/ −, and transgenic adenocarcinoma of mouse prostate), their age‐matched wild‐type controls, and 104 prostate core biopsies from human patients with different pathological lesions. Employing immunohistochemistry, differences in the levels of protein expression and spatial distribution of ZNT were evaluated as a function of the tumor stage. Results indicated that the expression of zinc importers (ZIP1, ZIP2, and ZIP3), which function to sequester zinc from circulation and prostatic fluid, was low to negligible in the membranes of the malignant prostate cells in both GEMM and human prostate tissues. Regarding zinc exporters (ZNT1, ZNT2, ZNT9, and ZNT10) that export excess zinc into the extracellular spaces or intracellular organelles, their expression was low in normal prostate glands of mice and humans; however, it was significantly upregulated in prostate adenocarcinoma lesions in GEMM and PCa patients. Together, our findings provide new insights into altered expression of ZNTs during the progression of PCa and indicate that changes in zinc homeostasis could possibly be an early‐initiation event during prostate tumorigenesis and a likely prevention/intervention target.